Field-Induced Nonlinearities in Silicon Waveguides Embedded in Lateral p-n Junctions - Castellan, Claudio; Franchi, Riccardo; Biasi, Stefano; Bernard, Martino; Ghulinyan, Mher; Pavesi, Lorenzo (Frontiers in Physics, 2019)
Silicon waveguides embedded in lateral p-n junctions show field-induced optical nonlinearities. By properly polarizing the junction, these can be used to achieve electro-optic modulation through the Direct Current Kerr effect. In addition, these enable second-order nonlinear processes such as the electric-field-induced second harmonic generation (EFISHG). In this work, we study in detail electro-optic effects in integrated silicon microresonators and demonstrate experimentally a field-induced resonance wavelength shift. This process is due to both the DC Kerr effect and the plasma-dispersion effect. By means of finite element method simulations, these effects are properly modeled and their contributions are accurately disentangled. The strength of the equivalent second-order nonlinear coefficient that would have provided the same electro-optic effect is about 16 pm/V. This result is comparable with that of materials possessing an intrinsic second order nonlinearity, and is one order of magnitude stronger than the most recent measurements of strain-induced Pockels effect in silicon.